Implementation of Artificial Neural Networks with Learning Vector Quantization (LVQ) Algorithm for Detecting Fingerprint Characteristics - Yessi Mardiana; Toibah Umi Kalsum (Penerbit Jurnal Indonesia, 2021)
The purpose of implementing Artificial Neural Networks (ANN) with the Learning Vector Quanzition (LVQ) algorithm is to be used as a fingerprint identifier. So with this application can determine who owns the fingerprint in accordance with the database that has. In identifying fingerprints, the Learning Vector Quanzition method is very good, because it can measure the value of a fingerprint image that has been taken either by using a camera or scanner. In identifying fingerprints, it is expected that the fingerprint image input into the database should be from a photo or scanner that has clear and bright results, because this will affect the fingerprint search in the futures.